Classification of Nanomaterial’s Risky Properties on the Aspect of Human Safety - Járdán, Eszter; Zákányiné Mészáros, Renáta (International Journal of Engineering and Management Sciences, 2021)
Due to their unique properties the application of nanomaterials continuously extends thus these appear for several industries. The industrial application of nanomaterials became significant during the last decades. As a result of the intensive development, our knowledge about the exact influence of nanomaterials for living bodies and human health is characterised by deficiency for both short and long time. Nanomaterials able to be entered to the living organism through several ways then invade to the circulatory system and the lymphatic system, reach the organs and can induce various kind of damages and serious diseases as a result of their different appearance, physical and chemical properties. Legislation in Hungary and in the European Union seems to be incomplete. There is no document which summarizes and details the risky factors and parameters in case of a risk assessment.  Our aim was to develop a criterion system considering the risks related to the use and contact of nanomaterials based on their physical, chemical and biological properties, which criterion system could provide basic principle for a risk assessment thereby make the industrial processes safer both for the employees and those who are in the vicinity.